Eksplorasi Praktik Pengasuhan Ibu dalam Pencegahan Stunting pada Bayi dan Balita di Kabupaten Kolaka - Nur Afni; Elma Elmika; Hardiyanti Alawiyah Nur (JURNAL KESEHATAN TERAPAN, 2026)
Stunting has long-term impacts on the quality of human resources and is related not only to nutritional intake but also to maternal caregiving practices. This study aims to explore maternal caregiving practices in preventing stunting in infants and toddlers in Kolaka District, Kolaka Regency, Southeast Sulawesi. This qualitative study, using a descriptive phenomenological design, involved 15 mothers with children aged 0-59 months, selected purposively. Data were collected through in-depth interviews and analyzed using thematic analysis with triangulation and member checking to ensure data validity. Five main themes were identified: the meaning of a healthy child, breastfeeding and complementary feeding practices, health service utilization, socio-cultural influences, and economic barriers and adaptive strategies. Mothers tend to assess their children's health based on their activity levels, while nutritional practices are influenced by economic conditions and family support. Stunting prevention is multidimensional and therefore requires a holistic and contextual approach involving families and health workers.